The performance of hybrid GPS and GLONASS - Baker, David Frederick (2001)
In recent years, the market served by satellite positioning systems has expanded exponentially. It is stimulated by the needs of an ever increasing number and variety of scientific, business and leisure applications. The dominant system is the USA's GPS, or Global Positioning System. However, GPS is not a panacea for all positioning tasks, in any environmental situation. For example, two of the fastest growing applications, vehicle tracking and personal location, operate in an often harsh signal reception environment. This can be so severe that even with the current 29 working satellites, GPS may struggle to perform. In exceptional circumstances it can fail to provide a positioning service at all.